Exploring Teachers’ Use of Technology in Classrooms of Bilingual Students - Daniel, Mayra C.; Cowan, John E. (GIST – Education and Learning Research Journal, 2012)
This article presents results of an investigation that documents teachers’ perceptions of the contribution of technology use in classrooms of bilingual learners. Study questions asked how teachers perceive teacher-made digital movies impact learning, and what situational factors delimit technology infusion. Data gathered in focus groups and surveys indicate teachers perceive appropriate technology gives bilingual students greater access to academic language. Results strongly suggest that school administrators control access to technology.